Efeito das poliaminas sobre a lipoperoxidação induzida por neurotoxinas em encéfalo de ratos - Bellé, Nádia Aléssio Velloso (2004)
Polyamines, among other functions, are considered to act as a free radical scavenger and antioxidant. The quinolinic acid, sodium nitroprusside and iron stimulate production of free radicals and consequent lipid peroxidation, by diverses mechanisms. In the present study we investigated the effects of polyamines, spermine and spermidine, on thiobarbituric reactive species (TBARS) production – an index of lipid peroxidation – induced by quinolinic acid, sodium nitroprusside, iron/EDTA system and free iron in rat brain. Spermine and spermidine, in the minor concentrations tested (nM), did not had a significant effect on basal lipid peroxidation or on quinolinic acid-induced lipid peroxidation. Nevertheless both polyamines, in micromolar concentrations, inhibited quinolinic acid-induced TBARS production; being spermine more efficient than spermidine. Spermine and spermidine also inhibited sodium nitroprusside-, iron/EDTA- and free iron-induced lipid peroxidation, but had a modest effect and only in high concentrations (mM). In addiction, in the presence of MK-801, quinolinic acid-induced lipid peroxidation was considerably more inhibited by polyamines. Arcaine did not affect the reducer effect of polyamines. The present findings suggest that the observed effects of polyamines are not related to the activation of NMDA receptor but with their free radical scavenger properties.